Usefulness of continuous actigraph monitoring in the assessment of the effect of corticosteroid treatment for Duchenne muscular dystrophy: a case report - Shiba, Naoko; Nakamura, Akinori; Nishizawa, Hitomi (Journal of Physical Therapy Science, 2016)
[Purpose] This study evaluated the effect of corticosteroid treatment on the daily activity of a patient with Duchenne muscular dystrophy using an actigraph and examined whether this method produces the same results as the conventional motor-function evaluation methods. [Subject and Methods] A patient with 5 year-old Duchenne muscular dystrophy was recruited. An actigraph was attached to his waist to measure the energy expenditure and the number of steps taken by him during a period of two weeks, 14 days before and 14 days after corticosteroid administration. The outcomes of these measurements were compared with the results of conventional motor-function evaluation methods—the 10-m run test, 6-minute walk test, and North Star Ambulatory Assessment—on his next visit. [Results] The actigraph data for energy expenditure and the number of steps taken correlated well with the results of the above-mentioned conventional motor-function tests, and the value of each data point improved after corticosteroid administration. [Conclusion] An actigraph was effectively used to non-invasively measure consecutive daily activity for four weeks. It was easily done and the results were consistent with conventional motor-function evaluation methods.